THE SPIRITUAL-PHILOSOPHICAL LEGACY OF IBN SINA AS PER NEWLY ESTABLISHED FINDINGS - Izzatullayeva Gavhar Normurotovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
In the following article the spiritual-philosophical legacy of Ibn Sina as per newly established findings were revealed based on the recent studies conducted in the Oriental and Western countries. New different approach is applied based on the regional preferences.